Effect of torque ratio on speed regulating start - Meng, Qingrui; Chenghao, Zhao; Zuzhi, Tian (Industrial lubrication and tribology, 2018)
Purpose Friction pairs of the hydro-viscous drive speed regulating start device should be designed based on the rated torque. To obtain design basis of the rated torque of the hydro-viscous drive speed regulating start device, studies on effect of torque ratio (a ratio of the load torque to the rated torque) on speed regulating start were carried out theoretically and experimentally. Design/methodology/approach Under different torque ratio, the modified Reynolds, the thermal energy and the viscosity-temperature equations were solved simultaneously by using finite element method to reveal variation laws of the oil film load capacity and torque transmission during the starting process. Then, speed regulating start experiments were carried out to study the following performance of the output speed. Findings The results show that oil film thickness decreases with the increase of the torque ratio; when oil film thickness is less than 0.05 mm, oil film temperature increases rapidly with the decrease of oil film thickness, which eventually deteriorates performance of the speed regulating start; when the torque ratio decreases to about 0.3, output speed shows a better following performance. Originality/value It indicates that, to acquire a better speed regulating start, the rated torque of the hydro-viscous drive speed regulating start device should not be less than three times of the load torque. Achievements of this work provide theoretical basis for optimal design of the friction pairs of the hydro-viscous drive speed regulating start device.